A generic ground dynamics model for ground handling evaluations - Koçak, G.; Şansal, K.; Sağıroğlu, S.; Kargin, V. (My University, 2018)
This paper demonstrates a generic ground dynamics model for modeling and simulating landing gear systems. Physics based model is developed in MATLAB-Simulink® environment and it is integrated to a non-linear 6-DOF helicopter model which is constructed in an in-house comprehensive analysis code, TAI Originated Rotorcraft Simulation (TOROS). Other than simulating the helicopter motion after touchdown, this model is also capable of trimming the helicopter on ground, which is useful for determining landing and take-off capabilities of a helicopter on either a flat or a sloped surface. This method can show whether the control ranges are adequate or not during the design stage, which is a troublesome task during preliminary design. In this study, slope-landing analyses of a light utility helicopter is demonstrated together with dynamics of a generic landing gear. The effect of ground on non-uniform inflow parameters, which is capable of modelling inclined ground effect, is included into the non-linear mathematical model using a finite state approach. Results show that, finite state ground effect model affected the control margins and main rotor flapping during slope landing and take-off analyses. In addition, rotational degree of freedom is added to the wheel component, which can be utilized not only for trimming and linearizing the helicopter on ground with/without airspeed but also for performing different ground-handling evaluations (e.g. high-speed taxiing, rolling take-off etc.). Moreover, by using this mathematical model, spin-up loads during run-on landings can be calculated, landing distance to full stop can be found and failure simulations (e.g. flat tire) can be performed